Palau : Detailed Assessment Report on Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report ;, 2009)
Palau's detailed assessment report on Anti-Money Laundering (AML) and Combating the Financing of Terrorism (CFT) has been examined. Palau has strengthened its AML/CFT legislative framework that has been in place since 2001 with the amendments to the Money Laundering and Proceeds of Crime Act of 2001 (MLPCA) and the Financial Institutions Act of 2001, as well as the enactments of the Counter-Terrorism Act of 2007 and the Cash Courier Disclosure Act of 2007. The offense of money laundering is criminalized in the MLPCA.